1996
DOI: 10.1128/jcm.34.7.1711-1716.1996
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of diphtheria toxin gene, tox, and its regulatory element, dtxR, in Corynebacterium diphtheriae strains causing epidemic diphtheria in Russia and Ukraine

Abstract: Diphtheria toxin (tox) and its regulatory element (dtxR) from 72 Corynebacterium diphtheriae strains isolated in Russia and Ukraine before and during the current diphtheria epidemic were studied by PCR-single-strand conformation polymorphism analysis (PCR-SSCP). Twelve sets of primers were constructed (eight for tox and four for dtxR), and three regions within tox and all four regions of dtxR showed significant variations in the number and/or sizes of the amplicons. Two to four different SSCP patterns were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…Therefore, it is concluded that the currently used vaccine is still appropriate for diphtheria prevention in Indonesia. The result is similar to the finding of Nakao et al (1996), which showed that the decrease in vaccine efficacy was not the primary cause of the large diphtheria outbreak in Russia.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, it is concluded that the currently used vaccine is still appropriate for diphtheria prevention in Indonesia. The result is similar to the finding of Nakao et al (1996), which showed that the decrease in vaccine efficacy was not the primary cause of the large diphtheria outbreak in Russia.…”
Section: Discussionsupporting
confidence: 89%
“…The dtxR gene was amplified and sequenced using the protocol from Nakao et al . and the TAQ PCR core kit (Qiagen, Courtaboeuf, France). Amino‐acid sequences were deduced from nucleotide sequences using EMBOSS software (http://www.mobyle.pasteur.fr) .…”
Section: Methodsmentioning
confidence: 99%
“…PCR. Two sets of primers targeting the A and B subunits of the diphtheria toxin gene were used to detect C. diphtheriae: primers Tox 1 (ATCCACTTTT AGTGCGAGAACCTTCGTCA) and Tox 2 (GAAAACTTTTCTTCGTACCA CGGGACTAA) (248 bp; A subunit) and primers Dipht 6F (ATACTTCCTGG TATCGGTAGC) and Dipht 6R (CGAATCTTCAACAGTGTTCCA) (297 bp; B subunit) (10)(11)(12). These primers were synthesized on a DNA synthesizer (ABI model 380A The Perkin-Elmer Corp., Norwalk, Conn.).…”
Section: Methodsmentioning
confidence: 99%